THE DEVELOPMENT OF PBL (PROBLEM BASED LEARNING) E-MODULE ON THE BIODIVERSITY OF EAST KALIMANTAN TO ENHANCE CRITICAL THINKING SKILLS OF HIGH SCHOOL STUDENTS - Kolow, Jullya Christin; Sulisetijono, Sulisetijono; Rohman, Fatchur; Maasawet, Elsje Theodora (Universitas Tanjungpura, 2024)
This research aims to develop an Electronic Module (E-module) that focuses on the diversity of living things in East Kalimantan based on PBL in an effort to improve the critical-thinking skills of valid, practical, and effective high school students. ADDIE development model with stages of analysis, design, development, implementation, and evaluation. E-modules are validated by material experts, teaching materials/media, learning tools, and biology education practitioners before being given to the experimental class. Data collection techniques through questionnaires and critical thinking skills tests by conducting pretests and post tests. Data analysis through t test. The results obtained by the product have validity of: 100% for material experts; 100% for media experts; 97.91% for learning device experts; 96.42% for education practitioners; 91.27% for individual tests; 88.00% for small group test; and 86.00% for field tests. For its effectiveness, which is with a value of 0.000.05, it is said to be effective and has a significant effect.